Feasibility analysis on building air-condition system renovation: Thailand case study - Bancha Sreewirote; Atthapol Ngaopitakkul (My University, 2019)
Energy efficiency improvement in existing buildings has been an interesting issue for researcher especially in heating, ventilation, and air conditioning (HVAC) system that appear to take up the large proportion of energy consumption. So, this paper aims to present an analysis on renovation measure to improve energy efficiency in building air-condition system. The study has been done using multi-purpose building in Thailand as a case study. The analysis of proposed renovation measurement will be done in both energy performance and economic perspective. Standard from Thailand building energy code is also taken into consideration when selecting equipment for replacement. The obtained result has indicated the suitability of proposed measure application in building with significant energy efficiency improvement and attractive economic parameter.
Keywords: Building code; Green Building; Building Energy and Comfort Optimization